2001
DOI: 10.1038/84808
|View full text |Cite
|
Sign up to set email alerts
|

A candidate prostate cancer susceptibility gene at chromosome 17p

Abstract: It is difficult to identify genes that predispose to prostate cancer due to late age at diagnosis, presence of phenocopies within high-risk pedigrees and genetic complexity. A genome-wide scan of large, high-risk pedigrees from Utah has provided evidence for linkage to a locus on chromosome 17p. We carried out positional cloning and mutation screening within the refined interval, identifying a gene, ELAC2, harboring mutations (including a frameshift and a nonconservative missense change) that segregate with pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
392
5
7

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 503 publications
(417 citation statements)
references
References 42 publications
13
392
5
7
Order By: Relevance
“…Further investigations are needed to determine whether ELAC2 can function as a general nuclear cofactor or scaffold protein in the TGF-b/Smad pathway. Using a genomewide screen together with positional cloning, ELAC2 was identified as a candidate prostate cancer susceptibility gene (Tavtigian et al, 2001). However, the association of ELAC2 with prostate cancer has been questioned in several publications (Wang et al, 2001;Shea et al, 2002).…”
Section: Elac2 Potentiates Tgf-b/smad Signaling D Noda Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…Further investigations are needed to determine whether ELAC2 can function as a general nuclear cofactor or scaffold protein in the TGF-b/Smad pathway. Using a genomewide screen together with positional cloning, ELAC2 was identified as a candidate prostate cancer susceptibility gene (Tavtigian et al, 2001). However, the association of ELAC2 with prostate cancer has been questioned in several publications (Wang et al, 2001;Shea et al, 2002).…”
Section: Elac2 Potentiates Tgf-b/smad Signaling D Noda Et Almentioning
confidence: 99%
“…However, it cannot be excluded that missense variants are more easily degraded than the wild type, resulting in a decreased TGF-b/Smad signaling. Furthermore, it remains possible that loss or decreased ELAC2 expression or functional inactivation through mutations in N-terminal half of ELAC2 gene might be found in other tumors because ELAC2 is ubiquitously expressed (Tavtigian et al, 2001). Recently, FAST-1 was reported to block the transactivation of androgen receptor (Chen et al, 2005a).…”
Section: Elac2 Potentiates Tgf-b/smad Signaling D Noda Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Six prostate cancer susceptibility loci (HPC1 at 1q24-25 (Smith et al, 1996), PCAP at 1q42-43 (Berthon et al, 1998), HPCX at Xq27-28 (Xu et al, 1998), CAPB at 1p36 (Gibbs et al, 1999), HPC20 at 20q13 (Berry et al, 2000) and HPC2 at 17p12 (Tavtigian et al, 2001)) and two candidate susceptibility genes (HPC2/ELAC2 at 17q (Tavtigian et al, 2001) and RNASEL at 1q24-25 ) have been reported.…”
mentioning
confidence: 99%
“…While some studies have debated the merit of haplotype analysis over single-SNP analysis [Chapman et al, 2003;Tzeng and Roeder, 2006], simulation studies [Akey et al, 2001;Morris and Kaplan, 2002;Rosenberg et al, 2006] have demonstrated haplotype procedures are more powerful than single-SNP procedures when either the causal polymorphism is not genotyped (which is highly likely) or when multiple causal polymorphisms act in cis fashion in the haplotype region. Studies provide empirical evidence of this latter event occurring in many genetic diseases, such as prostate cancer [Tavtigian et al, 2001].…”
Section: Introductionmentioning
confidence: 99%